2001
DOI: 10.1110/ps.46001
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical consequences of the perdeuteriation of glutathione S‐transferase from S. japonicum

Abstract: Glutathione S-transferase (GST) from Schistosoma japonicum has been prepared in both normal protiated (pGST) and fully deuteriated (dGST) form by recombinant DNA technology. Electrospray mass spectrometry showed that the level of deuteriation in dGST was 96% and was homogeneous across the sample. This result is attributed to the use of a deuterium-tolerant host Escherichia coli strain in the preparation of the protein. 10 heteroatom-bound deuteriums (in addition to the carbon-bound deuteriums) were resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
28
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
(35 reference statements)
7
28
2
Order By: Relevance
“…The CD spectrum of the GST dimer showed predominantly α-helical structure analogous to published data [28]. The CD spectra of HRV-A34, HRV-B14 and HRV-C3 VP1 demonstrated the presence of well-folded secondary structure, with broad minima between 208–220 nm indicative of mixed β-sheet and α-helical structure.…”
Section: Resultssupporting
confidence: 76%
“…The CD spectrum of the GST dimer showed predominantly α-helical structure analogous to published data [28]. The CD spectra of HRV-A34, HRV-B14 and HRV-C3 VP1 demonstrated the presence of well-folded secondary structure, with broad minima between 208–220 nm indicative of mixed β-sheet and α-helical structure.…”
Section: Resultssupporting
confidence: 76%
“…These observations are in accordance with previous studies where deuterated proteins have been found to be less stable to heat denaturation 15, 16, 17. Hattori et al 18.…”
supporting
confidence: 93%
“…There is relatively little information available on the effect of deuterium substitution on macromolecules 9, 15, 16, 17, 20. While this study shows consistent and reproducible effects of protein and solvent deuteration on TTR tetramer stability, isotope effects such as these are generally rather subtle and unpredictable.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Since the carbon source (glucose) was not deuterated, the expected level of deuteration was in the vicinity of 90% rather than 100% [11]. For the wild-type form of EI Ntr , the predominant form isolated was both phosphorylated at the active site and gluconoylated at the site of the His tag [12] (calculated mass of the H form = 66,969.8)(Table I).…”
Section: Methodsmentioning
confidence: 99%